1995
DOI: 10.1177/019262339502300301
|View full text |Cite
|
Sign up to set email alerts
|

Cause-of-Death Assignment at the National Center for Toxicological Research

Abstract: The system for assigning cause of death in animal studies of carcinogenicity at the National Center for Toxicological Research (NCTR) is described. An empirical study of the NCTR's experience with its current cause-of-death assignment system based on selected representative experiments is reported. Issues investigated include the degree of confidence associated with histologic cause-of-death assignment, potential age-, dose-, and sex-related differences in assigned grades of certainty of cause of death, and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Although the fatal neoplastic lesions were distributed in this study as described in previous reports of carcinogenicity studies using Sprague-Dawley derived rats [2,6], the incidence of fatal neoplasms was relatively low in this study, probably because there were more cases of chronic progressive nephropathy causing earlier death. The tumor incidences in males and females of both groups in this study were comparable with those reported by Muraoka et al [10], but much higher than in Prejean et al [12] who reported incidences of 34% and 58% in males and females, respectively.…”
Section: Discussionmentioning
confidence: 45%
“…Although the fatal neoplastic lesions were distributed in this study as described in previous reports of carcinogenicity studies using Sprague-Dawley derived rats [2,6], the incidence of fatal neoplasms was relatively low in this study, probably because there were more cases of chronic progressive nephropathy causing earlier death. The tumor incidences in males and females of both groups in this study were comparable with those reported by Muraoka et al [10], but much higher than in Prejean et al [12] who reported incidences of 34% and 58% in males and females, respectively.…”
Section: Discussionmentioning
confidence: 45%
“…103,104,131,225 Cause of Death (COD, CCOD) Assignment Determination of COD or CCOD, as illustrated in Table 1, can be expected to be important to the aims of aging studies in mice. The National Center for Toxicological Research (NCTR) developed a system for grading the certainty of cause of death, or cause of morbidity, in the case of moribund animals as follows: 128 If a particular neoplasm (or other pathological condition) can be identified by the examining pathologist as the most likely reason for the animal's death or removal, then it is reported as the probable cause of death. At most, one probable cause of death may be assigned.…”
Section: Grading Of Lesionsmentioning
confidence: 99%
“…EOL pathologies were then determined through standardized necropsies of each animal and neoplastic processes, separated into hematopoetic and non-hematopoietic classes, were graded according to Ikeno et al (2003). Grading the severity of neoplastic and non-neoplastic lesions facilitated estimations of disease burden and cause-of death-assignment criteria (Kodell et al, 1995) allowed assessment of contributing causes of moribundity.…”
Section: Introductionmentioning
confidence: 99%